2018
DOI: 10.1093/infdis/jiy695
|View full text |Cite
|
Sign up to set email alerts
|

Blood Viral Load in Symptomatic Congenital Cytomegalovirus Infection

Abstract: Background Viral loads (VLs) frequently are followed during treatment of symptomatic congenital cytomegalovirus disease, but their predictive value is unclear. Methods Post hoc analysis of 2 antiviral studies was performed. Seventy-three subjects were treated for 6 weeks and 47 subjects were treated for 6 months. Whole blood VL was determined by real-time polymerase chain reaction before and during therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 32 publications
1
36
1
8
Order By: Relevance
“…Viral load levels in EDTA blood were more than 10 4 -fold lower than in buccal swabs (Fig 3, S3 Table), consistent with the reduced sensitivity reported for assays based on dried blood spots [22,[25][26][27][28]. A recent study on symptomatic cCMV infections even revealed that CMV DNA levels were undetectable in 11% of whole blood samples of clinically symptomatic patients further questioning congenital CMV screening approaches based on blood samples [29]. Although median viral load levels did not differ significantly in the swab samples obtained during screening and confirmation, one caveat of our study is that the comparison to viral load levels in blood and urine was restricted to the confirmatory analysis.…”
Section: Discussionsupporting
confidence: 77%
“…Viral load levels in EDTA blood were more than 10 4 -fold lower than in buccal swabs (Fig 3, S3 Table), consistent with the reduced sensitivity reported for assays based on dried blood spots [22,[25][26][27][28]. A recent study on symptomatic cCMV infections even revealed that CMV DNA levels were undetectable in 11% of whole blood samples of clinically symptomatic patients further questioning congenital CMV screening approaches based on blood samples [29]. Although median viral load levels did not differ significantly in the swab samples obtained during screening and confirmation, one caveat of our study is that the comparison to viral load levels in blood and urine was restricted to the confirmatory analysis.…”
Section: Discussionsupporting
confidence: 77%
“…Lanari et al found that neonatal blood CMV load correlated with the likelihood of developing sequelae at 12 months of age [9]. Marsico et al reported the deterioration of hearing function to be uncommon in infants who consistently tested negative for CMV viremia from 2 weeks through 6 months after commencing treatment [10]. In contrast, Ross et al found no correlation between blood CMV load and hearing dysfunction in a cohort of 135 infants with congenital CMV infection [11].…”
Section: Discussionmentioning
confidence: 99%
“…The role of the viral load (VL) at birth has been recently investigated to determine whether it could be a reliable marker of disease severity or could predict long-term outcomes; its role in identifying children who will develop complications in their first years of life has also been studied. The VL may be influenced by several factors, such as the timing of intrauterine infection, the PCR assay used, the quality and quantity of immunological response, and potential antiviral treatment [ 75 ].…”
Section: Neonatal Screening and Diagnosismentioning
confidence: 99%
“…The largest available dataset of blood VL at birth was collected by Marsico et al in 2018; their study aimed to explore the effect of antiviral therapy on viremia. Among symptomatic newborns, a higher viral load seems to correlate with some markers of active diseases, such as thrombocytopenia and transaminitis [ 75 ]. The researchers were unable to find a threshold above which there is a greater risk of SNHL, and they also reported that the individual VL does not predict the hearing outcome; nevertheless, children treated for six months had a higher probability of hearing improvement if their viral load at birth was low.…”
Section: Neonatal Screening and Diagnosismentioning
confidence: 99%